Geometrie dei territori, etica e nuova economia - Peretti, Alberto (Scienze del Territorio, 2018)
A territory is a place with soul. To characterise a territory is not enough to define boundaries and the horizontality of the relationships that exist. A territory is a centre of vertical forces through which history, culture, knowledge, lifestyle, vocations have been deposited. Work is the soul of Italian territory. Each territory has a specific working DNA, a genius faber that expresses a way of working that is a synthesis of being able to do and being able to be, the art of life inside production patterns. Thanks to the work it is possible to harmonise diversity through communication. The power of a territory depends on its capacity to develop integration and cohesion between its different businesses, starting from the identification of a common working identity.